1986
DOI: 10.1099/00221287-132-7-2023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osmotic Stress on the Ultrastructure and Viability of the Yeast Saccharomyces cerevisiae

Abstract: Exposure of the yeast Saccharomyces cerevisiae to hypertonic solutions of non-permeating compounds resulted in cell shrinkage, without plasmolysis. The relationship between cell volume and osmolality was non-linear; between 1 and 4 osM there was a plateau in cell volume, with apparently a resistance to further shrinkage; beyond 4 osM cell volume was reduced further. The loss of viability of S. cerevisiae after hypertonic stress was directly related to the reduction in cell volume in the shrunken state. The pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
5

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 19 publications
7
75
1
5
Order By: Relevance
“…These data demonstrated that effects of osmotic stress on mean cell volume of yeast cells of lager and ale strains were inter-strain dependent. The effect of osmotic stress on mean cell volume was in agreement with the findings of Morris et al 28 with the exception of strain LCC 70. They provided evidence that increases in wort osmotic pressure produced shrinkage in the yeast cells.…”
Section: )Jjigx Sj Swqsxmg Wxviww Sr Qier Gipp Zspyqi Sj Pekiv Erh Epsupporting
confidence: 82%
See 4 more Smart Citations
“…These data demonstrated that effects of osmotic stress on mean cell volume of yeast cells of lager and ale strains were inter-strain dependent. The effect of osmotic stress on mean cell volume was in agreement with the findings of Morris et al 28 with the exception of strain LCC 70. They provided evidence that increases in wort osmotic pressure produced shrinkage in the yeast cells.…”
Section: )Jjigx Sj Swqsxmg Wxviww Sr Qier Gipp Zspyqi Sj Pekiv Erh Epsupporting
confidence: 82%
“…Data originating from the ESEM in situ studies were consistent with those of Morris et al 28 ( Figure 1, micrographs A through C). Although, their studies differed with respect to the S. cerevisiae strain employed, the concentrations and types of hypertonic solutions used and the duration of the experiments.…”
Section: (-7'977-32supporting
confidence: 79%
See 3 more Smart Citations